Women health worker\'s views about the screening and management program for domestic violence: a qualitative research - Yalda soleiman Ekhtiari; Fereshtah Majlessi; Mohsen Shams; Abbas Rahimi foroushani (Tehran University of Medical Sciences, 2010)
Background: Health care providers have important role in identification and management of domestic violence against women. The purpose of this study was to explore views and ideas of the women health worker about the screening and management programs related to domestic violence against women, their benefits and barriers and introducing the appropriate interventions for removing the barriers.       Materials and methods: This qualitative study was held through six focus group discussions and three in-depth interviews by the participation of fifty-six women who had provided reproductive health care of South Tehran, Rey and Eslamshahr Health Networks. The health care providers' views about domestic violence screening and management were extracted, categorized and analyzed.   Results: The majority of health care providers were aware of the importance of identifying and management of domestic violence cases in health care facilities. Respondents felt that they have responsibility to screen for domestic violence. Major barriers to domestic violence screening and management included perceived lack of time and place, insufficient knowledge and skills related to domestic violence screening and management, insufficient personnel and referral services. Conclusion: : Improvement of identifying and management of domestic violence in health care settings by removing the barriers to screening and improvement of referral and supportive services, can lead to decreasing in domestic violence against women cases.